Enhancing marital relationship through national emotive behavior therapy - Alejaga, Rebecca Martinez (2008)
This is an exploratory study that attempts to help distressed wives overwhelmed with relational problems cope with the stresses of their marital life. The study sought to answer whether counseling distressed wives alone will be effective in enhancing marital relationship of couples-at risk. Five distressed wives volunteers from Quezon City having serious marital relational problems were interviewed based on the previously given predetermined criteria from a list of distressed wives strongly recommended by friends and associates for intervention. The Rational Emotive Behavior Therapy (REBT) was used in the study. The result showed that REBT technique was indeed effective in all its 5 counseling cases.